Association between lipid profile and endothelial dysfunction as assessed by the reactive hyperemia index. (17th February 2021) - Norimatsu, Kenji; Gondo, Koki; Kusumoto, Takaaki; Motozato, Kota; Suematsu, Yasunori; Fukuda, Yusuke; Kuwano, Takashi; Miura, Shin-Ichiro
ABSTRACT: Introduction: We investigated the associations between endothelial dysfunction (ED) as evaluated by the reactive hyperemia index (RHI) obtained using Endo-PAT2000® and atherosclerotic risk factors in patients who underwent coronary artery angiography (CAG). Methods: The subjects consisted of 191 patients who were clinically suspected to have CAD and underwent CAG, and in whom we could perform Endo-PAT2000®. We divided the patients into ED (RHI<1.67, n = 71) and non-ED (RHI≥1.67, n = 120) groups. Results: The ED group was significantly older and showed a higher ratio of low-density lipoprotein cholesterol (LDL-C) to high-density lipoprotein cholesterol (HDL-C) (L/H) than the non-ED group. A multivariate logistic regression analysis was performed to examine the associations between the presence of ED and age, gender, and BMI in addition to L/H. Age [odds ratio (OR) = 1.03, p = .02] and L/H (OR = 1.64, p = .01) were identified as significant independent markers of the presence of ED. Next, we divided 122 patients with statin treatment into ED (n = 40) and non-ED (n = 82) groups. The ED group tended to have higher L/H and lower HDL-C than the non-ED group. HDL-C (OR = 0.95, p = .01) and age (OR = 1.05, p = .04) were identified as independent markers of the presence of ED. Conclusions: L/H was an independent marker of the presence of ED in patients without dyslipidemia. In addition, among patients with statin treatment, HDL-C was an independent marker of the presence of ED.